Interaction with nucleic acids and stimulation of the viral DNA polymerase by the herpes simplex virus type 1 major DNA-binding protein. - Ruyechan, W T (1984)
The interaction of the herpes simplex virus type 1 (HSV-1) major DNA-binding protein, infected-cell polypeptide 8 (ICP8), with nucleic acids has been examined by a filter-binding assay and electron microscopy. Filter-binding assays done over a broad pH range indicated that the optimum pH for the protein-DNA interaction is approximately 7.6. Heat inactivation studies showed that ICP8 is stable at temperatures up to 40 degrees C with a rapid loss of binding activity on incubation at 45 degrees C and above. Competition binding experiments have established the following relative affinities of ICP8 for the following nucleic acids: single-stranded HSV-1 DNA congruent to bacteriophage fd DNA greater than polyriboadenylate much greater than double-stranded HSV-1 DNA congruent to d(pCpT)5. Observation of negatively stained ICP8-single-stranded DNA complexes indicated that ICP8 binds along the length of the DNA in a regular repeating fashion. The average width of these complexes is 9.3 +/- 0.8 nms. Finally. Finally, addition of purified ICP8 to HSV-1 DNA polymerase reactions resulted in a stimulation of the viral polymerase activity.